2017
DOI: 10.3390/s17020408
|View full text |Cite
|
Sign up to set email alerts
|

Formal Uncertainty and Dispersion of Single and Double Difference Models for GNSS-Based Attitude Determination

Abstract: With multi-antenna synchronized global navigation satellite system (GNSS) receivers, the single difference (SD) between two antennas is able to eliminate both satellite and receiver clock error, thus it becomes necessary to reconsider the equivalency problem between the SD and double difference (DD) models. In this paper, we quantitatively compared the formal uncertainties and dispersions between multiple SD models and the DD model, and also carried out static and kinematic short baseline experiments. The theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The data processing for obtaining the residual time series used in RCM was divided into two steps. In the first step, the baseline (between the two antennas) solutions are estimated with integer ambiguity resolution by single difference algorithm [18,21,22]. In the second step, the daily solutions of baseline components (average of all the single epoch solutions on a day) are substituted into single-differenced observation equations to generate residuals for each satellite and for each epoch.…”
Section: Residual Correlation Methods (Rcm)mentioning
confidence: 99%
“…The data processing for obtaining the residual time series used in RCM was divided into two steps. In the first step, the baseline (between the two antennas) solutions are estimated with integer ambiguity resolution by single difference algorithm [18,21,22]. In the second step, the daily solutions of baseline components (average of all the single epoch solutions on a day) are substituted into single-differenced observation equations to generate residuals for each satellite and for each epoch.…”
Section: Residual Correlation Methods (Rcm)mentioning
confidence: 99%
“…The asymptotic analysis further demonstrated that using this multi-antenna GNSS receiver with a common clock, the pitch solutions of the SD algorithm were significantly superior to that of the DD algorithm. The dispersions of the pitch solutions from the SD algorithm were five times smaller than that from the DD algorithm [7]. These advantages allow using SD observables for attitude determination and research in other fields such as multipath [8] and stochastic models [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, such approach would not solve the problem of receiver clock bias which still needs to be estimated. With common receiver clock technology, single-difference models can be used to simplify the complexity and reduce the influence of uncorrelated noise [18]- [20]. The phase double difference refers to the instantaneous difference between the phase (single) difference observations of two different satellites [21].…”
Section: Introductionmentioning
confidence: 99%